With or Without Monism? A Roadmap to the Contemporary Appeal of Hegel’s Metaphysics (Revista Eletrônica Estudos Hegelianos, 2022)
The aim of this article is to provide a roadmap to assess the contemporary appeal of Hegel’s metaphysics. I will take the contemporary debate between “metaphysical”, “revised-metaphysical” and “post- Kantian” or “transcendental” interpretations of Hegel as a framework. I will claim that, more or less explicitly, all of the readings involved in the debate establish the contemporary interest of Hegel’s metaphysics by comparing it to a specific kind of philosophical theory, either present or absent in the wider contemporary (Anglo-American) philosophical conversation. Paragraphs 2 and 3 will be devoted to understanding these metaphilosophical commitments, presenting a brief reconstruction of the history of the consideration of metaphysics in XX- and XXI-century Anglo-American philosophy, and a brief presentation of the three main interpretations in the debate. In paragraph 4, I will provide insights on whether Hegel’s notion of metaphysics actually corresponds to one of those suggested in the debate, and whether it could consequently be considered of contemporary relevance. I will hold that Hegel’s metaphysics not only exceeds all of the three interpretations in the debate, but also contains insights that challenge the contemporary meta-philosophical assumption of what should be “in” and what should be “out” in metaphysics